2017
DOI: 10.1371/journal.pone.0181440
|View full text |Cite
|
Sign up to set email alerts
|

High anti-human cytomegalovirus antibody levels are associated with the progression of essential hypertension and target organ damage in Han Chinese population

Abstract: Human cytomegalovirus (CMV) infection is associated with hypertension and has been linked with the pathogenesis of increased arterial blood pressure (BP). Currently, whether CMV infection is associated with the progression of hypertension and hypertensive target organ damage (TOD) remains to be identified. We aimed to examine the relationship between CMV infection and the progression of hypertension and hypertensive TOD, which could provide clues on the possible mediating mechanisms, in the Han Chinese populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…However, the degree of MCMV infection at 9 months of age was significantly lower compared with that at 12 months of age. This finding was consistent with our previous population survey, which found that an increase in HCMV IgG titer was an independent risk factor for EH and target organ damage during HCMV infection ( 48 ). Another important reason may be that elevated blood pressure is a hemodynamic factor that induces vascular remodeling ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the degree of MCMV infection at 9 months of age was significantly lower compared with that at 12 months of age. This finding was consistent with our previous population survey, which found that an increase in HCMV IgG titer was an independent risk factor for EH and target organ damage during HCMV infection ( 48 ). Another important reason may be that elevated blood pressure is a hemodynamic factor that induces vascular remodeling ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies found that HCMV infection is associated with EH in patients of Kazakh and Han ethnicity in Xinjiang, and is associated with EH progression and target organ damage in patients of Han ethnicity, further supporting the correlation between HCMV and hypertension (24,25). We thus hypothesized that MCMV may be correlated to hypertension in mice through similar miRNA-induced mechanisms.…”
Section: Introductionmentioning
confidence: 60%
“…MicroRNAs (miRNAs) are highly conserved, single-stranded, non-coding small RNAs (19)(20)(21)(22)(23)(24)(25) nucleotides in length) that negatively regulate the expression of their target genes at the post-transcriptional level, by directly binding to the 3'-untranslated region (UTR) or 5'-untranslated region of their target mRNAs (19,20). Previous studies have shown that several miRNAs are involved in the development of primary hypertension (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…provided evidence of a relationship between CMV-specific immune responses and elevated blood pressure or arterial stiffness [22,[27][28][29][30]. However, no previous studies have investigated the relationship between blood pressure and CMV-specific T-cell immunity in PLHIV.…”
Section: Univariate Modelmentioning
confidence: 99%
“…CMV has been linked to increased risk of CVD-related morbidity and mortality in PLHIV [16], and increased magnitude of CMV-specific immune responses have been associated with subclinical cardiovascular disease [17][18][19]. The relationship between CMV-specific immune responses and risk of CVD has been thoroughly described in the general population [20][21][22][23][24][25][26][27][28][29][30], where CMV-specific immune responses are associated with risk of hypertension [22,[27][28][29][30], and CMV-specific T-cells have been shown to have a direct effect on the vascular endothelium [27,[31][32][33][34]. Thus, the relationship between CMV and adverse CVD-outcomes is not a unique feature of HIV infection, but may be increasingly relevant in this population due to high prevalence of CMV in PLHIV, higher immune responses against CMV, and increasing life expectancy leading to a higher lifetime CMV exposure in PLHIV.…”
mentioning
confidence: 99%